Influence of Service Quality and Store Atmosphere on Repurchase Intention at Najmia Beauty Cosmetics Store, Ungaran - Jihan Aurlya Candy; Andi Setiawan; Paniya (Politeknik Negeri Semarang, 2026)
The study aims to analyze the influence of service quality, and store atmosphere on repurchase intention of Najmia Beauty Ungaran Cosmetic Store. In this study using 100 samples who are customers of Najmia Beauty Ungaran Cosmetic Store, which were obtained through distributing questionnaires using purposive sampling techniques. The data obtained was processed using multiple linear regression analysis methods and SPSS 25 analysis tools. This study proves empirically that service quality (X1), and store atmosphere (X2), have a significant impact on repurchase intention (Y) of Najmia Beauty Ungaran Cosmetic Store. This study is expected to be a way out on determine the right marketing strategy in facing market rivalry in the store beauty by applying service quality, and store atmosphere to increase repurchase intention on Najmia Beauty Ungaran Cosmetic Store.